2003
DOI: 10.1002/jnr.10856
|View full text |Cite
|
Sign up to set email alerts
|

TIEG1 facilitates transforming growth factor‐β‐mediated apoptosis in the oligodendroglial cell line OLI‐neu

Abstract: Transforming growth factor-beta (TGF-beta) plays an important role during the period of developmental cell death in the nervous system. Using the oligodendroglial precursor cell line OLI-neu, we have previously established an in vitro system to analyze TGF-beta-mediated cell death on the molecular level. We could show that the Krüppel-like Zn-finger transcription factor TIEG1 was up-regulated after TGF-beta stimulation of OLI-neu cells and mimicked TGF-beta effects in these cells; i.e., overexpression of TIEG1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
1
24
0
2
Order By: Relevance
“…Because biological processes mostly involve additive events, TGF-b might lead to further events besides Fractin generation to completely induce apoptosis. Such an event is the Tieg1-induced down-regulation of Bcl-xl mRNA (Bender et al, 2004). Further analyses are required to clarify additive effects.…”
Section: Discussionmentioning
confidence: 97%
“…Because biological processes mostly involve additive events, TGF-b might lead to further events besides Fractin generation to completely induce apoptosis. Such an event is the Tieg1-induced down-regulation of Bcl-xl mRNA (Bender et al, 2004). Further analyses are required to clarify additive effects.…”
Section: Discussionmentioning
confidence: 97%
“…In this context, the functions of Klf10 and Klf11 have been studied in several cells that are TGF-beta-sensitive. Most of these studies have demonstrated that Klf10 and Klf11 mimic the effects of TGF-beta either in promoting apoptosis (Tachibana et al 1997;Ribeiro et al 1999;Bender et al 2004;Wang et al 2007;Jin et al 2007;Gohla et al 2008) or in decreasing proliferation (Cook et al 1998;Hefferan et al 2000b;Fernandez-Zapico et al 2003;Buck et al 2006). The pro-apoptotic effects of Klf10 and Klf11 seem to involve the transcriptional regulation of members of the Bcl-2 family.…”
Section: Role Of Klf10 and Klf11 In Apoptosis And Cell Cycle Progressionmentioning
confidence: 94%
“…They have been also identified in rat, monkey, pig and zebrafish genomes [14], [22]. TIEG proteins are involved in numerous processes, including, among others, proliferation, apoptosis, differentiation, cancer and circadian rhythms [17], [23], [24], [25], [26], [27], [28], [29], [30]. These proteins can function as either transcriptional repressors [31], [32] or activators [32], [33], [34], [35], depending on the cellular context, the promoter to which they bind and the coregulators with which they interact [33], [34], [35].…”
Section: Introductionmentioning
confidence: 99%